4D printing using FDM - Koh, Jethro Samuel Zi Yang (Nanyang Technological University, 2022)
The advancement of additive manufacturing and the need for flexible materials has brought along a new frontier of manufacturing called four dimensional (4D) printing. With time being the latest dimension to three dimensional (3D) printing, researchers are exploring how 3D printed objects can change structurally over time. This is done by using various stimulus to activate the internal stresses in the object resulting in various morphing capabilities. The purpose of the study is to find out how varying geometric parameters such as object’s height, size and grid pattern will affect its mechanical properties. The curvature and Young’s modulus of the object were measured to see the changes as the geometric parameters are varied. The results showed that all three geometric parameters affected the curvature and Young’s modulus to a certain degree. It is observed that the curvature of the object was greatly influenced by its height while the Young’s modulus was influence by the grid pattern.